Estudio de viabilidad para la linea de negocio yogurt griego organico con un diseño de sobre copa - Pajarito Montaño, Angie Lorena (Universidad Antonio Nariño, 2022)
Fruityolo is a sustainable enterprise, dedicated to the manufacture and marketing of liquid and Greek yogurt that is characterized by being organic and artisanal, which seeks to introduce into the market a new line of business, natural Greek yogurt in over cup with topping, in a presentation of 170 grams, this is made according to the needs of the consumer where he can choose between different types of milk such as: whole, lactose-free and /or skim, which at present there is no offer of this product under these conditions.